Distribution of ectoparasites of Canis lupus familiaris L. (Carnivora: Canidae) from Panama - Roberto Miranda C; Sergio Bermúdez C (Universidad de Cordoba, 2011)
Objetive. To determine the distribution of ectoparasites in dogs in Panama. Materials and methods. There were surveyed 720 canines belonging to 57 communities. Results. The results showed that 84% of the dogs were infested with at least one species of ectoparasite. Dogs from lowlands showed a higher percentage of parasitism and a greater biodiversity of parasites than dogs from highlands. There were found seven species of ticks, four species of fleas, two species of lice, and one specie of botfly. The ticks Rhipicephalus sanguineus, Amblyomma cajennense, A. ovale and the flea Ctenocephalides felis were widespread; however Ixodes boliviensis and Pulex simulans showed a much narrower geographic distribution and they were found only in dogs from highlands. The flea species Rhopalopsyllus cacicus and the tick Haemaphysalis juxtakochi were found for the first time in panamanian dogs. Conclusions. The environmental situation in Panama, can encourage that wildlife ectoparasites parasitized dogs in absence of their native hosts. This condition may increase transmission risk of some diseases where the ticks and fleas are vectors.